2000
DOI: 10.1124/mol.57.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Cellular Localization and Signaling Properties of the α1B- and α1D-Adrenoceptors by Agonists and Inverse Agonists

Abstract: The regulation of the cellular distribution and intracellular signaling properties of the alpha(1B)- and alpha(1D)- adrenoceptor (alpha(1)-AR) subtypes was examined in stably transfected Rat 1 fibroblasts. In unstimulated cells, alpha(1B)-AR expression was noted primarily on the cell surface. Treatment with phenylephrine induced internalization of the alpha(1B)-AR and promoted association with arrestin 2. The internalized alpha(1B)-AR colocalized with the transferrin receptor, an endosomal marker. In unstimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
94
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 22 publications
12
94
1
Order By: Relevance
“…In previous work, it has been shown that this receptor is expressed mainly in intracellular compartments (McCune et al, 2000;Chalothorn et al, 2002). We do not yet know the reason for this atypical localization pattern or if the regulatory activities of the ␣ 1D -AR are accomplished by these intracellular receptors.…”
Section: Discussionmentioning
confidence: 92%
“…In previous work, it has been shown that this receptor is expressed mainly in intracellular compartments (McCune et al, 2000;Chalothorn et al, 2002). We do not yet know the reason for this atypical localization pattern or if the regulatory activities of the ␣ 1D -AR are accomplished by these intracellular receptors.…”
Section: Discussionmentioning
confidence: 92%
“…3), and it will be interesting to see whether EBI2, like GPR109A, regulates distinct processes via these different effectors. Moreover, GSK682753A is able to suppress this activity with high potency and is thus an inverse agonist at both pathways, as seen in the ␣ 1D -adrenergic receptor, where the inverse agonist prazosin suppresses the activity of the G␣ q as well as the ERK pathways (36). On the other hand, the results are contradictory to the biased pharmacological profile of the ␤ 2 -adrenergic ligand ICI118551 that functions as an inverse agonist at the G␣ s pathway and as an agonist at the ERK pathway (37).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-1D AR subtype is known to be constitutively active and undergo phosphorylation or sequestration, as compared with the alpha-1A and alpha-1B AR subtypes (Gisbert et al, 2000;McCune et al, 2000). From these data, together with the high affinity of the alpha-1D AR subtype for catecholamines, it is possible that most of the alpha-1D AR subtype is sequestered or downregulated under sympathetically innervated conditions and that this process may be reversed by sympathetic denervation, resulting in an upregulation of the alpha-1D AR.…”
Section: N Taki Et Al Alpha-1d Adrenoceptors In Supersensitivity 653mentioning
confidence: 99%